1981
DOI: 10.5271/sjweh.2549
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson`s disease and occupational exposure to organic solvents, agricultural chemicals and mercury--a case-referent study.

Abstract: Parkinson`s disease and occupational exposure to organic solvents, agricultural chemicals and mercury--a case-referent study. by Ohlson C-G, Hogstedt CThe following article refers to this text: 2017;43(3):191-289

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 11 publications
0
27
1
Order By: Relevance
“…Occupational exposure to organic solvents was associated with increased risk of PD in two case-control studies [154,309] whilst in another study, the increased risk was confined to men [292]. Six other case-control studies, including the large (767 cases) European multicentre study [300], observed no association between organic solvents and PD [300,308,310,313,317,393]. One case-control study found an increased risk with longer duration of exposure (OR 3.59, 95% CI 1.26-19.26 for 20-30 years of exposure versus not exposed, p for trend 0.04) although no association was observed overall [381].…”
Section: Organic Solventsmentioning
confidence: 99%
“…Occupational exposure to organic solvents was associated with increased risk of PD in two case-control studies [154,309] whilst in another study, the increased risk was confined to men [292]. Six other case-control studies, including the large (767 cases) European multicentre study [300], observed no association between organic solvents and PD [300,308,310,313,317,393]. One case-control study found an increased risk with longer duration of exposure (OR 3.59, 95% CI 1.26-19.26 for 20-30 years of exposure versus not exposed, p for trend 0.04) although no association was observed overall [381].…”
Section: Organic Solventsmentioning
confidence: 99%
“…However, the relationship between occupational exposure to specific metals and PD has been examined infrequently in case-control studies with sizeable populations (table 1) [9][10][11][12][13][14]. Findings in these studies have also varied, most likely due to methodological differences, such as the locale and nature of the populations examined, the criteria used for the diagnosis of PD and the means of exposure assessment.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to mercury, Ohlson and Hogstedt [14], in a hospital-based case-control study in Sweden, found no group difference in occupational exposure to the metal. Seidler et al [10] reported elevated but nonsignificant Ever-exposure to lead associated with PD only by comparison with regional control group.…”
Section: Occupational Exposure To Specific Metals and The Risk Of Pdmentioning
confidence: 99%
“…The association of PD and mercury has been rarely reported or investigated [10]. Ohlson and Hogstedt [10] suggested a possi ble positive association (crude odds ratio, OR = 2.4; and 95% confidence intervals, Cl = 0.5-5.0) between mercury exposure and PD and other forms of parkinsonism, al though body burden mercury levels in their study subjects were not assayed.…”
Section: Introductionmentioning
confidence: 99%
“…Several environmental factors, like pre vious exposure to toxins, pesticides, virus and smoking, have been investigated in an attempt to elucidate the etiology of idio pathic Parkinson's disease (PD) [1][2][3][4][5][6][7][8][9][10]. Caine et al [1] postulated that PD and sev eral other related neurological conditions may be due to environmental damage to spe-ciftc regions of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%